Racial Differences in the Influence of Health Care System Factors on Informal Support for Cancer Care Among Black and White Breast and Lung Cancer Survivors. Issue 3 (July 2020) - Ellis, Katrina R.; Black, Kristin Z.; Baker, Stephanie; Cothern, Carol; Davis, Kia; Doost, Kay; Goestch, Christina; Griesemer, Ida; Guerrab, Fatima; Lightfoot, Alexandra F.; Padilla, Neda; Samuel, Cleo A.; et al.
Abstract : This retrospective, secondary qualitative analysis investigates whether health system factors influence social support among Black and white breast and lung cancer survivors and racial differences in support. These data come from race- and cancer-stratified focus groups (n = 6) and interviews (n = 2) to inform a randomized controlled trial utilizing antiracism and community-based participatory research approaches. Findings indicate social support was helpful for overcoming treatment-related challenges, including symptom management and patient-provider communication; racial differences in support needs and provision were noted. Resources within individual support networks reflect broader sociostructural factors. Reliance on family/friends to fill gaps in cancer care may exacerbate racial disparities. Abstract : Supplemental Digital Content is Available in the Text.